An activity-based parametric cost analysis for upcycling machining chips to produce feedstock for sustainable additive friction stir deposition - Sweta Baruah; Joshua Hoekstra; Tony Schmitz (Additive Manufacturing Letters)
With the growing emphasis on supply chain resilience and efficiency, manufacturers are increasingly exploring sustainable material reuse strategies. One promising approach is the upcycling of machining chips into usable feedstock for additive friction stir deposition (AFSD), a solid-state additive manufacturing process. AFSD has demonstrated potential for integrating into hybrid manufacturing workflows, offering advantages such as reduced material waste and enhanced process sustainability. However, for chip upcycling to produce AFSD feedstock to be viable, its production cost must be accurately assessed and compared to conventional feedstock options. Estimating these costs poses challenges due to the complexity of the upcycling process and its associated variables. This paper presents a cost modeling framework for the production of upcycled bars from machining chips, specifically as AFSD feedstock. The proposed model incorporates key cost factors such as material preparation, compaction, and processing efficiency. A case study is conducted to compare the cost of upcycled feedstock with commercially available AFSD feedstock, providing insights into the economic feasibility of chip upcycling for AFSD applications.